2015
DOI: 10.1002/pca.2585
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Profiling of Bioactive Phenolic Compounds in Argan (Argania spinosa) Leaves by Combined Microextraction by Packed Sorbent (MEPS) and LC‐DAD‐MS/MS

Abstract: The obtained results could represent a first step towards a complete characterisation of the argan plant, its bioactive profiling and the valorisation of its by-products as a source of potentially beneficial bioactive molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…More than 50 polyphenolic compounds have been identified by UHPLC-ESI-QTOF-MS under negative electrospray ionization conditions [M − H] − based on their retention times, molecular weights, and mass ( m/z ) fragmentation patterns. The study was focused on negative ionization mode [M − H] − because it is reported to be more sensitive for analysis of phenolic acids and flavonoids, compared to positive ionization mode [ 28 , 29 , 30 ]. The phenolic compounds in rosemary extracts were mostly flavonoids, phenolic acids, and terpenoids.…”
Section: Resultsmentioning
confidence: 99%
“…More than 50 polyphenolic compounds have been identified by UHPLC-ESI-QTOF-MS under negative electrospray ionization conditions [M − H] − based on their retention times, molecular weights, and mass ( m/z ) fragmentation patterns. The study was focused on negative ionization mode [M − H] − because it is reported to be more sensitive for analysis of phenolic acids and flavonoids, compared to positive ionization mode [ 28 , 29 , 30 ]. The phenolic compounds in rosemary extracts were mostly flavonoids, phenolic acids, and terpenoids.…”
Section: Resultsmentioning
confidence: 99%
“…S1 ). Thus, flavonol- O -glucosides also showed abundant [Y-H] − product ion at high collision energy [40] , [41] , [42] , [43] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These authors described a concentration of melatonin ranging from 0.005 to 0.9 ng g −1 . Likewise, Mercolini et al also observed the presence of melatonin in wine (0.4-0.5 ng mL −1 ) [57].…”
Section: Melatoninmentioning
confidence: 76%